Brother hood - McDonald, Janet 1954-2007 (Farrar, Straus and Giroux, 2004)
Sixteen-year-old Nate, an academically gifted student who attends an exclusive private boarding school, straddles two cultures as he returns home for occasional visits to see his family and "gangsta crew" in Harlem, New York.
"Frances Foster Books." -- Sixteen-year-old Nate, an academically gifted student who attends an exclusive private boarding school, straddles two cultures as he returns home for occasional visits to see his family and "gangsta crew" in Harlem, New York.
Keywords: Schwarze. USA; Gifted children -- Fiction; African Americans -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Harlem (New York, N.Y.) -- Fiction